Genetic influences on alcohol use across stages of development: GABRA2 and longitudinal trajectories of drunkenness from adolescence to young adulthood. (20th May 2013) - Dick, Danielle M.; Cho, Seung Bin; Latendresse, Shawn J.; Aliev, Fazil; Nurnberger, John I.; Edenberg, Howard J.; Schuckit, Marc; Hesselbrock, Victor M.; Porjesz, Bernice; Bucholz, Kathleen; Wang, Jen‐Chyong; Goate, Alison; et al.
Abstract Longitudinal analyses allow us to understand how genetic risk unfolds across development, in a way that is not possible with cross‐sectional analyses of individuals at different ages. This has received little attention in genetic association analyses. In this study, we test for genetic effects of GABRA2, a gene previously associated with alcohol dependence, on trajectories of drunkenness from age 14 to 25. We use data from 1070 individuals who participated in the prospective sample of the Collaborative Study on the Genetics of Alcoholism, in order to better understand the unfolding of genetic risk across development. Piecewise linear growth models were fit to model the influence of genotype on rate of increase in drunkenness from early adolescence to young adulthood (14–18 years), the change in drunkenness during the transition to adulthood (18–19 years) and the rate of change in drunkenness across young adulthood (≥ 19 years). Variation in GABRA2 was associated with an increase in drunkenness that occurred at the transition between adolescence and adulthood. The genotypic effect was more pronounced in females. These analyses illustrate the importance of longitudinal data to characterize how genetic effects unfold across development. The findings suggest that transitions across important developmental periods may alter the relative importance of genetic effects on patterns of alcohol use. The findings also suggest the importance of considering gender when evaluating genetic effects on drinking patterns in males and females.